Omnidirectional video coding using latitude adaptive down‐sampling and pixel rearrangement. Issue 10 (1st May 2017) - Lee, S.‐H.; Kim, S.‐T.; Yip, E.; Choi, B.‐D.; Song, J.; Ko, S.‐J.
Abstract : Projection of omnidirectional videos in the spherical domain onto the planar domain is required to utilise existing video compression techniques. Due to its simplicity, the equirectangular projection (ERP) method has been widely adopted for sphere‐to‐plane mapping. However, the coding efficiency of the ERP method is inefficient because the ERP video includes visual redundancies in the high latitude areas of the sphere. To solve this problem, this Letter presents an efficient data compression scheme that employs latitude adaptive down‐sampling followed by pixel rearrangement. Experimental results show that the proposed method can achieve a bitrate reduction of up to 28.9%, as compared with the ERP.